Development of an Information Technology-Enabled Learning Environment for Bataan Peninsula State University - et.al, Roda A. PangilinanPh.D, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research Information Technology-Enabled Learning Environment for Bataan Peninsula State University was developed to provide an easier and faster process of submission of class requirements and ratings of student works which will help the faculty members to manage their classes efficiently via intranet and an internet-based connection. It is capable of allowing the students to submit soft copies of their requirements such as major course output, laboratory exercises, case studies, and other projects. Faculty members are allowed to validate currently enrolled students, create classes, accept students in listed classes, post announcements through the content feeds, and maintain grading system per course and its rubrics of assessment. Finally, the application allows students to check announcements, requirements, and projects posted by the faculty member through the content feeds. The system was developed using PHP as the programming language, Apache for the webserver, MySQL as the Database Engine. It passes the user’s acceptability evaluation based on ISO 2510102011 with sub-criteria such as effectiveness, efficiency, satisfaction, freedom from risk, and context coverage.